2013
DOI: 10.1103/physrevb.88.081401
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Eliashberg function and electron-phonon coupling in doped graphene

Abstract: We investigate, with high-resolution angle-resolved photoemission spectroscopy, the spectral function of potassium-doped quasi-free-standing graphene on Au. Angle-dependent x-ray photoemission and density functional theory calculations demonstrate that potassium intercalates into the graphene/Au interface, leading to an upshift of the K-derived electronic band above the Fermi level. This empty band is what makes this system perfectly suited to disentangle the contributions to electron-phonon coupling coming fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
76
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(87 citation statements)
references
References 47 publications
9
76
2
Order By: Relevance
“…Hence, the Eliashberg function a 2 F(o, E, k) contains all we need to predict T c . It has been shown for Be 26 and also for graphene 27 that a 2 F(o, E, k) can be extracted from high-quality ARPES data. Regarding graphene, we have shown previously 27 that a 2 F(o, E, k) contains an isotropic contribution in both high-symmetry directions of two peaks for the graphene-derived optical phonons from G and K points while an extra low-energy peak appears in KM direction only.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the Eliashberg function a 2 F(o, E, k) contains all we need to predict T c . It has been shown for Be 26 and also for graphene 27 that a 2 F(o, E, k) can be extracted from high-quality ARPES data. Regarding graphene, we have shown previously 27 that a 2 F(o, E, k) contains an isotropic contribution in both high-symmetry directions of two peaks for the graphene-derived optical phonons from G and K points while an extra low-energy peak appears in KM direction only.…”
Section: Resultsmentioning
confidence: 99%
“…1 we show the dopant and carbon core level spectra probed in normal emission and grazing emission as it is displayed in the inset. This method allows to determine the carbon/metal stoichiometry and the location of the dopant atom (inside the Au/graphene interface or on top of graphene) via the relative photoemission intensities for normal and grazing emission 27 . From the ratios shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods allow us to study the interface structure of the dopant/hBN system, i.e., whether the dopant preferably is above or under hBN, and to probe the unoccupied states, respectively. The crucial point in this approach is that hBN is on a Au substrate that readily ionizes the deposited alkali atoms, which is somewhat similar for doped graphene on metal substrates, where ARPES and density functional theory (DFT) have shown that a part of the electron charge is transferred to the metal [8,24]. The present case is different from the graphene case, in the sense that graphene accepts a large fraction of the alkali atom's charge while hBN does not.…”
Section: Introductionmentioning
confidence: 60%
“…The lack of electronic states at or close to the Fermi level also limits the chemical activity of hBN. In contrast to carbon materials, where ionic [8], covalent [9], and substitutional [10] doping have been successfully carried out, the interaction of potassium with bulk hBN does not result in charge transfer to the electronic states of hBN [11] owing to the large energy band gap. This insulating and chemically inert behavior is exploited in novel 2D devices which use hBN as a substrate for graphene in order to attain high electronic mobilities.…”
Section: Introductionmentioning
confidence: 99%